Outcome analysis of 300 prostate cancer patients treated with neoadjuvant androgen deprivation and hypofractionated radiotherapy. - Higgins, G; McLaren, D; Kerr, G; Elliott, T; Howard, G (2006)
PURPOSE: Neoadjuvant androgen deprivation and radical radiotherapy is an established treatment for localized prostate carcinoma. This study sought to analyze the outcomes of patients treated with relatively low-dose hypofractionated radiotherapy. METHODS AND MATERIALS: Three hundred patients with T1-T3 prostate cancer were treated between 1996 and 2001. Patients were prescribed 3 months of neoadjuvant androgen deprivation before receiving 5250 cGy in 20 fractions. Patients' case notes and the oncology database were used to retrospectively assess outcomes. Median follow-up was 58 months. RESULTS: Patients presented with prostate cancer with poorer prognostic indicators than that reported in other series. At 5 years, the actuarial cause-specific survival rate was 83.2% and the prostate-specific antigen (PSA) relapse rate was 57.3%. Metastatic disease had developed in 23.4% of patients. PSA relapse continued to occur 5 years from treatment in all prognostic groups. Independent prognostic factors for relapse included treatment near the start of the study period, neoadjuvant oral anti-androgen monotherapy rather than neoadjuvant luteinizing hormone releasing hormone therapy, and diagnosis through transurethral resection of the prostate rather than transrectal ultrasound. CONCLUSION: This is the largest reported series of patients treated with neoadjuvant androgen deprivation and hypofractionated radiotherapy in the United Kingdom. Neoadjuvant hormonal therapy did not appear to adequately compensate for the relatively low effective radiation dose used.